Rosetfiblens »anatomi« - Skjødt, Annagrete (Kuml, 2009)
The “anatomy” of the rosette fibula Rosette or thistle fibulas have always attracted attention by virtue of their size and exclusiveness. They are richly decorated with, for example, gilt sheet metal and inlaid pieces of coloured glass. Also in terms of craftsmanship these are complicated pieces as each fibula consists of 40-60 different individual components. It was apparently only women of high status who were buried with one or, in rare instances, two examples. In Oscar Almgren’s classic work on the Northern European fibula types, rosette fibulas are assigned to his group VII – fibulas with a high catch plate – and thereby to the Late Roman Iron Age (AD 150/160 – 375). There is general agreement today that rosette fibulas in Denmark should be dated primarily to C1b (AD 210/220 – 250/260), i.e. generally a short period of use of just one to two generations, and neither has any wear been observed on these artefacts. Rosette fibulas are widespread across a very large area: Denmark, Norway, Sweden, Northeast Germany, Poland, the Baltic countries and Moldavia. The present article involves a systematic examination of their method of manufacture and material composition with the aim of distinguishing both geographic groups and possible workshop districts. As a basis for this, an overview has been produced of Danish rosette fibulas, defined here as having at least two rosettes. Denmark is represented by the greatest number, with 60 examples. Of these, 58 originate from inhumation graves, one from a cremation grave and one from a pit. Their geographic distribution is not even but is linked with particular areas such as Northern Jutland around the Limfjord, Southwestern Jutland and the southern part of Central Jutland, Eastern Funen, Eastern Zealand and the southwestern part of Bornholm (fig. 1). In the list of finds, numbers 1-24 are from Jutland, 25-29 are from Funen, 30- 57 from Zealand and 58-60 are from Bornholm. In the rest of Scandnavia these artefacts are rare, with seven examples from Norway and nine from Sweden. In studies of rosette fibulas it is practical to focus separately on functional and ornamental aspects. The former comprises the elements of spring, bow and pin, which are necessary in order for the fibula to be used as a simple safety pin, but also the technique and the metals used is included here. The ornamentation comprises, conversely, many different elements such as, for example, the upper and lower surfaces of the box-shaped spring cover as well as the various rosettes terminating in moulded knobs. Furthermore, the tension lugs, which sit between the spring and the ends of the spring cover. The ornamentation of the bow comprises rosettes and cuffs whereas the catch plate may be fitted with a band and ornamentation on the actual catch itself. The decorative parts are normally made of sheet metal, which is often gilded (figs. 2a, b). Correspondence analyses The most important results of a series of correspondence analyses show that the material can be divided up into four geographic groups (figs. 9-10). Group 1 is very homogeneous and has its primary distribution on Zealand. Almost half (46%) of all the examples from Zealand fall into this group. They are very well preserved and are represented by many variants. They are made of silver, and other special features are that the bow and catch plate are cast in one piece. The upper surface of the spring cover is constructed of three successive vaulted rosettes (form 1), which are also seen on the bow. The rosettes are wreathed with flattened silver discs and the moulded knobs are encased within sheet silver. Group 2 is similarly represented primarily by examples from Zealand and should be considered as a sub-group of group 1. Group 3 is represented by a few fibulas from Jutland and a single example from Funen. Most of these are poorly preserved and therefore only present in a few variants. Characteristic features, which should be highlighted, include three rosettes on the spring cover, the bow and the catch plate cast in one piece, a flat silver disc around the rosettes and a bow of bronze. The choice of metal follows primarily the Jutish tradition in which bronze is most prominent, whereas the manufacture is according to the tradition on Zealand. In the analysis, this cluster locates itself mid between groups 1 and 2 on the one side and group 4 on the other. Group 4 has its distribution in Jutland as 62.5% of all the fibulas from Jutland fall here. There are also two from Funen. The most important features are that the bow and catch plate are not cast in one piece and the bow consists typically of bronze plated with babbitt metal, whereas the catch plate is often of silver and is, in several cases, ornamented with engraved lines. The pin itself is of bronze or copper, the same applies to the tension lugs. The upper surface of the spring cover comprises a rectangular bronze band clad with a rosette that sits as a central feature around the lower end of the bow. The bow is ornamented with flat rosettes and typically with a domed roundel of blue glass. Basically it is, as already suggested, possible to speak of two traditions, an Eastern Danish and a Jutish. With regard to the identification of possible workshop groups, it can be tentatively concluded that there was one on Zealand and two in Jutland. The five rosette fibulas from Funen show, conversely, no indication of the existence of independent workshops but should be seen rather as a mixture of Jutish and Zealand craft traditions. Typological classification of rosette fibulas and their distribution On the basis of the primary studies, a typological classification has been carried out of the 36 best examples within six types. As the number of examples is modest, the classification should be taken with some reservation. Only the dominant types will be dealt with in more detail here; these are types 1 and 4. Again, it is the geographic distribution that is apparent, in that type 1 appears on Zealand whereas type 4 is Jutish. Due to its special construction, type 3 is similarly commented upon. The distribution of the other types is, conversely, very scattered as is apparent from the table (fig. 11). Type 1 is defined by having five vaulted rosettes. They are attached by way of a cast pin or a long through rivet and terminating in a moulded knob. The bow and catch plate are cast in one piece. Type 4 is characterised by having three rosettes, including the central rosette. The two rosettes on the bow have inlaid glass roundels or are made of vaulted sheet metal. The spring cover is most often rectangular. Type 3 comprises just three examples. These are characterised by the angle of the bow being greater than 90 degrees, they lack the high catch plate and have a triangular catch-plate cover with a hook to take the pin. The rosettes are soldered to the edge of the spring cover, and they can be circular or semi-circular and of sheet metal with or without blue glass inlays. All three examples come from Southwestern Jutland. Rosette fibulas have a very wide geographic distribution, from Norway in the north to the Black Sea in the south, and from Jutland in the west to the Baltic countries in the east. These spectacular ornaments must have belonged to the elite and their distribution indicates the extensive nature of the various networks at that time and therefore give a good insight into the extent of social mobility. One potential form of contact could have been marital alliances. These may have played an important role for the aristocracy in its wish to maintain their social status as well as their economic and political power. In other aspects of the archaeological record there are indications that women from the aristocratic Himlingeøje families were apparently married off to men in Tuna in Sweden. Rosette fibulas of Scandinavian type have, furthermore, been found in the Ukrainian-Rumanian Moldau area north of the Black Sea, which is perhaps also an indication of marital alliances. Unfortunately, the distinctive and easily recognisable rosette fibulas were only in use for a short period of 30-50 years, after which it again becomes more difficult to evaluate the extent of exchange within the large Germanic area. The work presented here is based on primary observations of most of the rosette fibulas from Denmark. It demonstrates clearly that there is much new information to be obtained from these elitist ornaments. At the same time, the importance is demonstrated yet again of renewed and primary studies of the existing archaeological record. Neither is there any doubt that more sophisticated methods of scientific analyses will, in the future, definitely be able to reveal much more new information and thereby contribute to a better and more sophisticated understanding of the significance of rosette fibulas as an important social marker within the aristocratic environs of the Iron Age. Annagrete Skjødt † Redigeret af Jørgen Lund Institut for Antropologi, Arkæologi, og Lingvistik Aarhus Universitet